A Program Evaluation of an Inclusive Model for Training Pre-Service General Education Teachers to Work with Students with Special Needs - Cannon, Joanna E.; Swoszowski, Nicole C.; Gallagher, Peggy; Easterbrooks, Susan R. (Journal of the American Academy of Special Education Professionals, 2012)
The purpose of this study was to evaluate a program using an inclusive model (e.g., course work in special education and special education liaison support) on the beliefs, practices, and skills of pre-service middle and secondary general education teachers (n = 26) regarding their preparedness to work with students with special needs. A pre- and post-survey, adapted from the General Education Teachers’ Beliefs and Attitudes toward Planning for Mainstreamed Students (G-TBAP; Schumm, Vaughn, Gordon, & Rothlein, 1994) survey, was administered to participants in an urban research university in the Southeast. The graduate students were resurveyed while they were completing their practicum experiences. Statistically significant results were found in the post-survey indicating the inclusive model was effective for this program. Multiple dependent t-test analyses indicated that the overall beliefs, practices, and skills were improved for participants, "t(25) = -4.156, p = 0.000. Limitations and future directions are discussed.